2016
DOI: 10.1080/14681366.2016.1208265
|View full text |Cite
|
Sign up to set email alerts
|

Modest witness(ing) and lively stories: paying attention to matters of concern in early childhood

Abstract: This article considers the role of early childhood education within these uncertain times of human induced climate change. It draws from feminism and environmental humanities to experiment with different ways of becoming-with the world. By bringing together Donna Haraway's figure of the Modest Witness and Deborah Bird Rose's notion of witnessing, the article rethinks what it means to 'observe' in terms of ethical response-ability and matters of concern. Data from a multisensory and multispecies ethnography are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
55
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(59 citation statements)
references
References 27 publications
0
55
0
3
Order By: Relevance
“…A growing body of feminist scholarship, engaged in experimental modes of research, foregrounds a concern with materiality and affect (Blaise et al, 2016;Hohti, 2018;Holmes & Jones, 2016;Osgood & Robinson, 2019;Sandvik, 2010;St.Pierre & Jackson, 2014;Taylor et al, 2013). The potential of taking up creative and uncertain research practices demonstrated by this growing field of enquiry acted as an inspiration to investigate what carrier-bag practices of storytelling (Haraway, 2004, p. 127) might offer to this study.…”
Section: Sitting In a Corner Watching Groupworkmentioning
confidence: 99%
See 1 more Smart Citation
“…A growing body of feminist scholarship, engaged in experimental modes of research, foregrounds a concern with materiality and affect (Blaise et al, 2016;Hohti, 2018;Holmes & Jones, 2016;Osgood & Robinson, 2019;Sandvik, 2010;St.Pierre & Jackson, 2014;Taylor et al, 2013). The potential of taking up creative and uncertain research practices demonstrated by this growing field of enquiry acted as an inspiration to investigate what carrier-bag practices of storytelling (Haraway, 2004, p. 127) might offer to this study.…”
Section: Sitting In a Corner Watching Groupworkmentioning
confidence: 99%
“…Some passages are presented in italics; which can be read as diffractive moves throughout the article. Haraway (2004Haraway ( , 2016 offers SF as a research philosophy, inspiring researchers to make use of methodological entrances and experimental practices (Blaise, Hamm, & Iorio, 2016;Taylor, Blaise, & Giugni, 2013, Osgood, 2019. We take SF-philosophy as both a concept to understand research, and a tool to assist us in analysing groupwork processes.…”
Section: Introductionmentioning
confidence: 99%
“…An example of this is to question that observation takes place only through vision and hearing, and realise that affect, such as thinking/feeling, is also included in observation (Otterstad & Nordbrønd, 2015). Also Blaise, Hamm and Iorio (2016) rethink what observation is about, not by questioning the use of the senses, but rather through presenting different ways of documenting in preschool. They argue that pedagogical documentation, pedagogical narration, and, especially, creating 'lively stories' (p. 9) can be ways of moving away from observational practices that presuppose the possibility of obtaining knowledge about children through objective observations and moving towards practices that are able to also take into account 'human and more-than-human encounters' (p. 39).…”
Section: Challengingmentioning
confidence: 99%
“…Lively stories, as presented in the article by Blaise, Hamm and Iorio (2016) (see Pedagogical Documentation), are principally suggested as a way of working with ecological issues in preschool. But what if lively stories could be a way of working with anything, and everything?…”
Section: and Challenging Preschool Documentation Through Lively mentioning
confidence: 99%
See 1 more Smart Citation